A Proposed Framework for Applying the National Standards of Quality Assurance in Higher Education in Sudan from the Teaching Staff's Perspective - Faculties of Business Administration - Alfatih Alamin Elfaki; Khedir Sidieq Mohamed; Mohamed Ahmed Hamato; Ahmed Idries Abdo (University of Science and Technology, Yemen, 2017)
This study aimed to clarify the importance of having national standards and their role in achieving quality, as well as establishing a framework for the actual application of national standards in quality assurance so as to achieve quality in higher education institutions. The researchers  followed a descriptive analytical method to achieve the objectives of the study and developed a questionnaire covering primary and secondary variables that have a role in the design of specific models to help in applying the national standards by the Sudanese universities. The questionnaire included one dependent variable; the effective application of national standards of quality assurance in higher education institutions, and the four main variables (independent) are: the national standards of quality assurance in higher education in Sudan, the standard of quality assurance, the standard of teaching and learning and the standard of scientific research and publication. The study revealed a number of conclusions: there were statistically significant differences in the extent of familiarity with the  national quality assurance standards in Sudan according to the academic rank of the  faculty members; there were also significant differences in the extent of compliance with the  national quality assurance standards in Sudan according to the academic rank of the faculty members; there was full agreement between the national standards for quality assurance in Sudan and the international standards for quality assurance; and  there were statistically significant differences in that the absence of specific models would have a negative impact on effective application of national standards of quality assurance in higher education in Sudan, according to the academic rank of the faculty members. Keywords: Quality, The program, Standards, University, Total quality management.